2015
DOI: 10.1016/j.taap.2015.09.006
|View full text |Cite
|
Sign up to set email alerts
|

Cadmium promotes the proliferation of triple-negative breast cancer cells through EGFR-mediated cell cycle regulation

Abstract: Cadmium (Cd) is a carcinogenic metal which is implicated in breast cancer by epidemiological studies. It is reported to promote breast cancer cell growth in vitro through membrane receptors. The study described here examined Cd-mediated growth of non-metastatic human breast cancer derived cells that lack receptors for estrogen, progesterone, and HER2. Treatment of triple-negative HCC 1937 cells with 0.1–0.5 μM Cd increased cell growth by activation of AKT and ERK. Accelerated cell cycle progression was achieve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(11 citation statements)
references
References 50 publications
0
11
0
Order By: Relevance
“…AKT is the intermediate molecule of various pathways, including EGFR. Upon inhibiting EGFR kinase activity with AG1478, the activity of AKT is reduced, as demonstrated by a reduction in the phosphorylation of AKT in colorectal adenocarcinoma (49), nasopharyngeal carcinoma (50) and breast cancer cells (51). In the present study, although GE treatment led to a reduction in the phosphorylation of EGFR and AKT, treatment with AG1478, an EGFR kinase inhibitor, in the HuCCA-1 cells reduced the phosphorylation of EGFR only, and not its downstream molecule AKT.…”
Section: Discussionmentioning
confidence: 99%
“…AKT is the intermediate molecule of various pathways, including EGFR. Upon inhibiting EGFR kinase activity with AG1478, the activity of AKT is reduced, as demonstrated by a reduction in the phosphorylation of AKT in colorectal adenocarcinoma (49), nasopharyngeal carcinoma (50) and breast cancer cells (51). In the present study, although GE treatment led to a reduction in the phosphorylation of EGFR and AKT, treatment with AG1478, an EGFR kinase inhibitor, in the HuCCA-1 cells reduced the phosphorylation of EGFR only, and not its downstream molecule AKT.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, their roles in promoting cell proliferation have been reported. For instance, activation of estrogen receptor by Akt and Erk mediated estrogen receptor has been reported to promote breast cancer cell proliferation [34]. Furthermore, Verdier-Sevrain et al have reported that the Erk signaling pathway is activated through non-genomic pathways in the physiological process of exogenous estrogen-induced keratinocyte proliferation [23].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies indicate that Cd promotes breast cancer cell growth, with some suggesting that it also promotes metastasis (Yang et al, 2004; Benbrahim-Tallaa et al, 2009; Siewit et al, 2010). Promotion of cell growth by Cd is described as a xenoestrogenic effect (Siewit et al, 2010; Ponce et al, 2013; Song et al, 2015) involving membrane receptors (Yu et al, 2010; Wei et al, 2015). Waalkes et al (2000) reported that chronic Cd treatment increased metastatic potential of sc-injected sarcomas in rats.…”
Section: Introductionmentioning
confidence: 99%